Next generation semiconductor based sequencing of bitter taste receptor genes in different pig populations and association analysis using a selective DNA pool‐seq approach. (20th July 2016) - Ribani, A.; Bertolini, F.; Schiavo, G.; Scotti, E.; Utzeri, V. J.; Dall'Olio, S.; Trevisi, P.; Bosi, P.; Fontanesi, L.
Summary: Taste perception in animals affects feed intake and may influence production traits. In particular, bitter is sensed by receptors encoded by the family of TAS2R genes. In this research, using a DNA pool‐seq approach coupled with next generation semiconductor based target resequencing, we analysed nine porcine TAS2R genes ( TAS2R1, TAS2R3, TAS2R4, TAS2R7, TAS2R9, TAS2R10, TAS2R16, TAS2R38 and TAS2R39 ) to identify variability and, at the same time, estimate single nucleotide polymorphism (SNP) allele frequencies in several populations and testing differences in an association analysis. Equimolar DNA pools were prepared for five pig breeds (Italian Duroc, Italian Landrace, Pietrain, Meishan and Casertana) and wild boars (5–10 individuals each) and for two groups of Italian Large White pigs with extreme and divergent back fat thickness (50 + 50 pigs). About 1.8 million reads were obtained by sequencing amplicons generated from these pools. A total of 125 SNPs were identified, of which 37 were missense mutations. Three of them (p.Ile53Phe and p.Trp85Leu in TAS2R4 ; p.Leu37Ser in TAS2R39 ) could have important effects on the function of these bitter taste receptors, based on in silico predictions. Variability in wild boars seems lower than that in domestic breeds potentially as a result of selective pressure in the wild towards defensive bitter taste perception. Three SNPs in TAS2R38 and TAS2R39 were significantly associated with back fat thickness. These results may be important to understand the complexity of taste perception and their associated effects that could be useful to develop nutrigenetic approaches in pig breeding and nutrition.